What Explains Correlates of Peer Victimization? A Systematic Review of Mediating Factors - Kretschmer, Tina (Adolescent Research Review, 2016)
Being accepted by peers is central to health and wellbeing among adolescents whereas being the subject of peer/bullying-victimization can be perceived as significant interpersonal stress, resulting in compromised adjustment concurrently and long-term. Unfortunately, little is known about mechanisms that explain why peer victimization goes “under the skin”. This systematic review aims to summarize the research on mediating pathways. A total of 65 articles were selected that explicitly examined mediation of associations between peer victimization in adolescence and concurrent and later outcomes. Most studies were based on North American and European samples and focused on internalizing or school-related outcomes. Mediation appears to be more stable by emotional states and symptoms than self-perceptions and attributions but results vary by outcome. Limitations concern the cross-sectional design of most studies, geographic restriction, and widespread use of self-reports for assessments of exposure, mediator, and outcome.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Academic; Externalizing; Internalizing; Mediation; Peer victimization; Systematic review